Developing female learners cognitive and moral metacognitive abilities through modified double-loop learning discussion strategy - Jasmin, Maria Lourdes Solis (College of Education, University of the Philippines Diliman, 2019)
Understanding the moral metacognitive abilities of female students on pornography viewing is a topic that has never been explored before. As such, this study aimed to (a) look into female adolescents beliefs and behaviors on pornography viewing, (b) examine their cognitive and metacognitive processing when faced with this moral issues and ( c ) determine if the Modified Double-Loop Learning Discussion Strategy (MDLDS) can increase their moral metacognitive abilities. It utilized a mixed-method approach including giving out the Moral Metacognitive Questionnaire on Pornography Viewing (MMQPV) to 267 public school senior high student and conducting interviews with 21 Grade 12 students. It also utilized a single-group pre-test post-test design to determine the effectiveness of MDLDS intervention program among 9 Grade 12 students. Results showed that many of them displayed high incongruence between their desired behavior and actual behavior when it came to watching pornography. When their moral judgment and moral action towards pornography was processed using cognitive approach, it was found out that they generally used mental shotcuts in the form of moral schema. Finally, this study has found out that the MDLDS program is effective in increasing the moral metacognitive abilities and producing more meaningful learning. This study then forwards an emergent framework supporting the cultivation of moral metacognitive thinking over cognitive strategies for processing moral issues.